ABNORMAL INFLORESCENCE MERISTEM1 Functions in Salicylic Acid Biosynthesis to Maintain Proper Reactive Oxygen Species Levels for Root Meristem Activity in Rice. Issue 3 (14th March 2017) - Xu, Lei; Zhao, Hongyu; Ruan, Wenyuan; Deng, Minjuan; Wang, Fang; Peng, Jinrong; Luo, Jie; Chen, Zhixiang; Yi, Keke
Abstract : Root meristem activity, which determines root growth and architecture, is maintained through the modulation of reactive oxygen species levels via a salicylic acid biosynthesis pathway in rice. Abstract: Root meristem activity determines root growth and root architecture and consequently affects water and nutrient uptake in plants. However, our knowledge about the regulation of root meristem activity in crop plants is very limited. Here, we report the isolation and characterization of a short root mutant in rice ( Oryza sativa ) with reduced root meristem activity. This root growth defect is caused by a mutation in ABNORMAL INFLORESCENCE MERISTEM1 ( AIM1 ), which encodes a 3-hydroxyacyl-CoA dehydrogenase, an enzyme involved in β-oxidation. The reduced root meristem activity of aim1 results from reduced salicylic acid (SA) levels and can be rescued by SA application. Furthermore, reduced SA levels are associated with reduced levels of reactive oxygen species (ROS ) in aim1, likely due to increased expression of redox and ROS -scavenging-related genes, whose increased expression is (at least in part) caused by reduced expression of the SA -inducible transcriptional repressors WRKY62 and WRKY76. Like SA, ROS application substantially increased root length and root meristem activity in aim1 . These results suggest that AIM1 is required for root growth in rice due to its critical role in SA biosynthesis: SA maintains root meristem activity through promoting ROS accumulation by inducing the activity of WRKY transcriptional repressors, which repress the expression of redox and ROS -scavenging genes.